2009
DOI: 10.1002/jmri.21706
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated phase‐contrast MR imaging: Comparison of k‐t BLAST with SENSE and doppler ultrasound for velocity and flow measurements in the aorta

Abstract: Purpose: To evaluate differences in velocity and flow measurements in the aorta between accelerated phase-contrast (PC) magnetic resonance imaging (MRI) using SENSE and k-t BLAST and in peak velocity to Doppler ultrasound. Materials and Methods:Two-dimensional PC-MRI perpendicular to the ascending and descending aorta was performed in 11 volunteers using SENSE (R ϭ 2) and k-t BLAST (2-, 4-, 6-, and 8-fold). Peak velocity, mean velocity, and stroke volume of the accelerated PC-MRI experiments were correlated. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 28 publications
7
12
0
Order By: Relevance
“…This is in consensus with previous studies applied in human medicine, which could show temporal blurring with k-t BLAST acceleration for stroke volume (Stadlbauer et al, 2009;Stadlbauer et al, 2010;Carlsson et al, 2011;van Ooij et al, 2013). This effect can be explained, as stroke volume is the sum of flow volumes over all heart phases.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This is in consensus with previous studies applied in human medicine, which could show temporal blurring with k-t BLAST acceleration for stroke volume (Stadlbauer et al, 2009;Stadlbauer et al, 2010;Carlsson et al, 2011;van Ooij et al, 2013). This effect can be explained, as stroke volume is the sum of flow volumes over all heart phases.…”
Section: Discussionsupporting
confidence: 73%
“…A first step generates an under-sampled image that would exhibit multiple fold-over artifacts if reconstructed conventionally. A second step, the training stage acquires an estimate of the novel, moving parts in the image and allows reconstruction of the image without aliasing (Stadlbauer et al, 2009;Attili et al, 2010;Stadlbauer et al, 2010;Carlsson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge about the high degree of redundancy in phase contrast velocity data has fuelled efforts to acquire Cartesian undersampled time-resolved data using parallel imaging or a combination of parallel imaging and spatiotemporal constraints [10-12]. These techniques have been limited by temporal blurring artefacts when using undersampling factors larger than 5 in both time-resolved 3D [13-15] and 2D phase-contrast CMR [11,16]. Recent improvements of reconstruction algorithms dedicated to phase-contrast imaging have enabled acceleration factors greater than 5 for 3D phase-contrast CMR of the carotid bifurcation [17].…”
Section: Introductionmentioning
confidence: 99%
“…k-t BLAST (Broad-use Linear Speed-up technique) is a method employed to reduces scan time using under-sampling of data in k-t space [8] and this technique has been used to accelerate 2D-flow measurements in vivo [9,10]. The 4D-flow application for k-t BLAST was described in a phantom by Marshall [11] and recently Stadlbauer et al found limitations with temporal blurring when comparing k-t BLAST with SENSE acceleration for 4D aortic flow measurements at 1.5 T [12].…”
Section: Introductionmentioning
confidence: 99%